PEMANFAATAN ARANG TEMPURUNG KEMIRI (Aleurites moluccana (L.) Willd.) SEBAGAI ADSORBEN PADA PEMURNIAN MINYAK KELAPA SAWIT MENTAH/CRUDE PALM OIL (CPO) - Eka Nuryanto; Dwi Ratih Askasari (Jurnal Penelitian Kelapa Sawit, 2018)
Crude Palm Oil (CPO) is the main product of the oil palm fresh fruit bunch processing results. Cooking oil can be made from CPO with through a process of refinery and fractionation. Has done research on the utilization of shell charcoal candlenut as the adsorbent for the refinery of CPO. The variables used in this study is the mass of the adsorbent (10, 15, 20, and 25 g), temperature variations (100, 110, 120, 130 and 140oC) and the stirring time variation (0.5, 1, 2, 2.5, and 3 hours). The parameters analyzed is the analysis of the levels of free fatty acids, the color, and β-carotene. The results showed that the lowest content of free fatty acids (ALB) at temperature treatment is obtained at 120 oC, shell charcoal candlenut mass 25 g (12.5% w/w the CPO), and long stirring 1 hour. As for the lowest color parameters obtained at the treatment temperature 130 °C, shell charcoal candlenut mass 15 g (7.5% w/w the CPO), and long stirring 1 hour. Shell charcoal candlenut can be used as adsorbents on refinery of CPO.